Analisis Pemodelan Arsitektur Enterprise Untuk Mendukung Sistem Informasi Akademik Dengan Metode Task Centered Desain Sistem - Hidayati Ami; Renny Maulidda Kom.; Ica Admiran Kom.; Sartika Oktavianti (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Data architecture describes the various types of data called data entities used in business enterprises. Application architecture illustrates the main application needed to manage the data and support the business functions of the company. Enterprise architecture illustrates the operational model of enterprise that includes aspects of business planning, business operations, automation up to the supporting information technology infrastructure. Methods Task Centered System Design (TCSD) is a method used to identify user needs and the needs of the task. TCSD method includes four stages of activity, namely identification, User-Centered Requirements Analysis, design as scenario, and walkthrough Evaluate. Excess use of this method is the design of the system and the program code generated properly - in strict accordance with user needs. Analysis modeling enterprise architecture to support academic information systems at STIK Siti Khadijah Palembang aimed at optimizing the performance of academic information system, reducing barriers between work units, reduce duplication of data, reducing operational costs, improving productivity and performance of employees in information sharing and cooperation between work units to improve quality academic services. Results of this research is the design of the enterprise architecture model of academic information systems. Keywords: Enterprise Architecture, Task Centered System Design, Academic Information System